2020
DOI: 10.3390/plants9070858
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Dihydrophaseic Acid Glucosides from the Florets of Carthamus tinctorius

Abstract: Carthamus tinctorius L. (Compositae; safflower or Hong Hua) has been used in Korean traditional medicine for maintaining the homeostasis of body circulation. Phytochemical investigation was performed on the florets of C. tinctorius by liquid chromatography–mass spectrometry (LC/MS), which afforded two dihydrophaseic acid glucosides (1 and 2). Isolated compounds were structurally confirmed using a combination of spectroscopic methods including 1D and 2D nuclear magnetic resonance and high-resolution ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Thus, the planar structure of 3 was established, as shown in Figure 2 . Finally, the absolute configuration at C-3 was assigned using quantum chemical ECD calculations [ 23 , 24 , 25 ]. Two possibilities with absolute configurations of 3 R and 3 S were calculated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the planar structure of 3 was established, as shown in Figure 2 . Finally, the absolute configuration at C-3 was assigned using quantum chemical ECD calculations [ 23 , 24 , 25 ]. Two possibilities with absolute configurations of 3 R and 3 S were calculated.…”
Section: Resultsmentioning
confidence: 99%
“…All searches were initially set in the gas phase, with a 10 kJ/mol energy window limit and a maximum of 10,000 steps to thoroughly explore all potential conformers. The Polak–Ribiere conjugate gradient protocol was established with 10,000 maximum iterations and a 0.001 kJ (mol Å) −1 convergence threshold on the rms gradient to minimize conformers [ 23 , 24 , 25 ]. Conformers proposed in this study (within 5 kJ/mol found in the MMFF force field) were selected for geometry optimization by Tmolex 4.3.1, with the DFT settings of B3-LYP/6-31+G(d,p).…”
Section: Methodsmentioning
confidence: 99%
“…A new flavonoid (saffloflavanside (1)), sesquiterpene (safflomegastigside (2)), and amide (saffloamide (3)), in addition to 22 known compounds from safflower were also isolated (Liu et al, 2022). Two dihydrophasic acid glycosides, dihydrophasic acid glucoside, which has anti-obesity effects, were also been isolated from C. tinctorius florets (Baek et al, 2020). Five new sesquiterpenoids (1-5) were isolated from the florets of safflower, which was named as (−)-(1R,4S,9S,11R)-caryophyll-8 (13)-en-14-ol-5one (1), (+)-(1R,4R,9S,11R)-caryophyll-8 (13)-en-14-ol-5-one (2), (−)-(3Z,1R,5S,8S,9S,11R)-5,8-epoxycaryophyll-3-en-14-O-β-Dglucopyranoside (3), (+)-(1S,7R,10S)-guai-4-en-3-one-11-O-β-Dfucopyranoside (4), and (−)-(2R,5R,10R)-vetispir-6-en-8-one-11-Oβ-D-fucopyranoside (5).…”
Section: Other Active Substancesmentioning
confidence: 99%
“…As part of our continuing natural product discovery program for the identification of novel bioactive compounds from miscellaneous natural resources [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ], we continued chemical and biological analyses of methanolic extracts of the fruiting bodies of D. confragosa , because the methanol extract of D. confragosa showed antibacterial activity against Helicobacter pylori strain 51 in our bioactivity screening. D. confragosa has rarely been investigated in terms of its chemical constituents.…”
Section: Introductionmentioning
confidence: 99%